Environmental Justice as a Human Right: Legal Tools for Climate Accountability - Amina Iqbal; Muhammad Atif Khokhar; Dr. Sami Ur Rahman (Indus Journal of Social Sciences, 2025)
Climate change presents an unprecedented threat to human rights, disproportionately affecting marginalized communities and exacerbating global inequality. This study explores the conceptualization of environmental justice as a human right and examines the legal tools available to ensure climate accountability at domestic, regional, and international levels. The research aims to highlight how a rights-based approach can reinforce climate governance and empower vulnerable populations through access to justice, legal remedies, and participatory frameworks. Adopting a doctrinal methodology, this study reviews constitutional provisions, international treaties, judicial decisions, and climate litigation trends to evaluate the effectiveness of current legal mechanisms. Key findings indicate that while several legal avenues such as environmental constitutionalism, human rights litigation, and international soft law offer potential for enforcing environmental justice, their practical impact is limited by enforcement gaps, jurisdictional constraints, and power asymmetries. Nonetheless, emerging jurisprudence and legal innovations show promise in bridging these gaps. The study concludes that recognizing environmental justice as a fundamental human right and strengthening legal accountability mechanisms are essential steps toward achieving climate justice and ensuring equitable environmental protection for present and future generations. Environmental justice has emerged as a crucial dimension of human rights discourse in the era of climate crisis. As climate change disproportionately affects marginalized and vulnerable populations, the demand for legal mechanisms to hold polluters accountable and protect communities has intensified. This article explores environmental justice as a fundamental human right and critically evaluates the legal tools available at domestic, regional, and international levels for enforcing climate accountability. It argues for a rights-based approach to climate governance, emphasizing legal empowerment, procedural safeguards, and judicial remedies as essential strategies for ensuring environmental justice.